Analisis Strategi Guru Pendidikan Agama Islam Dalam Pembentukan Karakter Siswa Kelas V Sekolah Dasar Islam Terpadu Hidayah Klaten - Rosyida Umma; Nur Hidayah; Lailla Hidayatul Amin (Edusifa: Jurnal Pendidikan Islam, 2025)
The results of this study indicate that the strategy implemented by Islamic Religious Education teachers in building student character at SDIT Hidayah Klaten for the 2021/2022 Academic Year includes the forms of character that are expected in Class V SDIT students, namely discipline, honesty, democracy, creativity, and responsibility. The strategy used by PAI teachers in building student character at SDIT Hidayah Klaten Tahun is that the teacher is a role model for students and the teacher evaluates students who are not good by intensely communicating with parents of students. The supporting factor during the process of implementing the teacher's strategy in building student character at SDIT Hidayah Klaten was that the implementation of the program was highly supported by the good performance of the principal, all teachers, staff and students as well as the existing curriculum. While the inhibiting factors during the process of implementing the teacher's strategy in building student character at SDIT Hidayah Klaten include: there are still some students who sometimes lack discipline in carrying out their duties, there is still a lack of tidiness and cleanliness, less optimal cooperation between teachers and less optimal Collaboration between the school and parents/guardians of students